Large Subserosal Leiomyoma with Omental and Bowel Adhesion Diagnosed during Pregnancy: A Case Report - Zeena Raad Helmi; Wassan Nori; Amenah Fadhil (AlQalam Journal of Medical and Applied Sciences, 2025)
Uterine leiomyoma (or fibroids), represent the most frequent benign tumor of the uterus among reproductive age women. We present a 35-year-old primigravida diagnosed with gestational diabetes coexisting with a uterine fibroid that caused no complaints during pregnancy. At 38 weeks and during a scheduled elective C-section, a right fundo-lateral wall fibroid measuring 11 x 10 cm in size, with multiple omental and bowel adhesions, was found. It started with severe bleeding, which was efficiently controlled by pressure, thus avoiding hysterectomy. A drain was left in situ. On the 10th post-operative day, she had a normal pelvic ultrasound and was scheduled for elective myomectomy 6 months later. This case report explores the challenges in reducing intra- and postoperative bleeding from a large leiomyoma.